Sharia Supervision Of Amil Zakat And Shodaqoh Institutions: Framwork And Reporting Of Supervision Results - Fielnanda, Refky (ILTIZAM Journal of Shariah Economics Research, 2022)
The purpose of this study was to determine the work framework of the Sharia Supervisor and the reporting of the results of the supervision of the Sharia Supervisory Board at the Insan Madani Amil Zakat Institution and BAZNAZ Jambi City.This research uses descriptive qualitative methods, with a field research approach. It was found that the work framwork of the Shari'ah Supervisor both at the Insan Madani Amil Zakat Institution and BAZNAZ Jambi City is to supervise the operational activities of the Amil Zakat Institution to comply with the provisions and principles of sharia. The difference lies in reporting the results of the supervision of the Shari'ah Supervisor where the Insan Madani Amil Zakat Institution reports the results to the Jambi Provincial BAZNAZ and then the Regional Office of the Ministry of Religion of Jambi Province periodically. Unlike the case with BAZNAZ Jambi City which reports the results of its supervision to the Regional Office of the Ministry of Religion, the Mayor, and the Governor.